O lugar da imagem: ANCINE, ANCINAV e o desafio da regulação do audiovisual no Brasil - Fornazari, Fabio Kobol (2007)
This research aims to analyze policies of public regulation, supervision and support to film industry in Brazil, regarding the establishment of ANCINE – National Agency of Cinema. It is studied under the perspective of contemporary shifts in the institutional framework of the Brazilian State and the need of undestanding the meaning of independent regulatory agencies in this country. Moreover, it proposes to evaluate the debate upon the shift in the profile and goal of the agency, towards a more strict regualtory perspective, since it was expected to be replaced by ANCINAV – National Agency of Cinema and Audiovisual, leading to the controversial way such a proposal was received by both the sectorial and political fields. We conclude by interpreting this Brazilian experience as the diffusion of an institutional apparatus, which articulates the sectorial policy, bringing about the sectorial longing for legitimacy, credibility and institutional stability, whilst limited by the opposition to enlarge its regulatory framework towards mass communication means.